Penerapan Konsep Suply Chain Management dalam Pengembangan Pola Distribusi dan Wilayah Pemasaran UMKM Desa Krambilsawit - Muhfiatun, Muhfiatun; Rudi Nugraha, Muh (UIN Sunan Kalijaga, Yogyakarta, Indonesia, 2018)
This research aims to formulate development strategies and regional distribution pattern of Small Medium Enterprises (SME) marketing Village Krambilsawit. Low productivity and the narrowness of the region of product marketing, requires that SMEC Village Krambilsawit doing repairs ranging from upstream to downstream processes. The use of the concept of supply chain management, where very precise in order to resolve the problems occurred at Krambilsawit village of SME. In this study researchers using qualitative and quantitative research methods. Data obtained from the results of the direct interview to the perpetrators of the SMEC Village Krambilsawit. As for the methods of analysis used to formulate policy that is by using SWOT analysis. From this research that the results obtained in order to develop patterns of distribution and marketing SME Krambilsawit Village area required the presence of revamping the Groove Commerce SMEC, i.e. by implementing two levels or three levels of channel to expand network marketing. The implications of the end, the author hopes this research could be a reference in developing patterns of distribution and marketing of SME Krambilsawit Village.Penelitian ini bertujuan untuk merumuskan strategi pengembangan pola distribusi dan wilayah pemasaran UMKM Desa Krambilsawit. Rendahnya produktifitas serta sempitnya wilayah pemasaran produk, mengharuskan UMKM Desa Krambilsawit melakukan perbaikan mulai dari proses hulu ke hilir. Penggunaan konsep supply chain management, dirasa sangat tepat guna menyelesaikan permasalahan yang terjadi pada UMKM Desa Krambilsawit. Dalam penelitian ini peneliti menggunakan metode penelitian kualitatif dan kuantitatif. Data diperoleh dari hasil waawancara secara langsung kepada pelaku UMKM Desa Krambilsawit. Adapun metode analisis yang digunakan guna merumuskan kebijakan yaitu dengan menggunakan analisis SWOT. Dari penelitian ini diperoleh hasil bahwa guna mengembangkan pola distribusi dan wilayah pemasaran UMKM Desa Krambilsawit maka diperlukan adanya pembenahan alur tata niaga UMKM, yakni dengan menerapkan two level chanel atau three level chanel guna memperluas jaringan pemasaran. Implikasi akhir, penulis berharap penelitian ini bisa menjadi acuan dalam mengembangkan pola distribusi dan wilayah pemasaran UMKM Desa Krambilsawit.